(NrYBAK IZ wNUTRIMORXQ(B: [(NpOWESTX(B]; s (N~ETYRE PUTI K PRO]ENI@(B: [(NrOMAN(B] / s - (NlE gUIN(B, (NuRSULAs ((NmOSKWA(B: s (N|KSMO(B, s, 2004)
(Nw \TOT TOM WO[LI PROIZWEDENIQ uRSULY lE gUIN(B, (NPRODOLVA@]IE ZNAMENITYJ hAJNSKIJ CIKL(B.s
(NoBDELENNYE(B, (NuHODQ]IE IZ oMELASA(B, (NiSTORIQ (B"(N[OBIKOW(B", (NtANCUQ gANAMs
rus
Keywords: (NpOWESTI I RASSKAZYs; (NnAU^NO(B-(NFANTASTI^ESKIJ ROMANs